Slope surface permanent temporary combined protection coiled material and preparation method and application thereof
Patent Information
- Application Number
- CN202611139090.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]1、土工膜及彩条布极易老化、被风掀起、施工低效,固定节点易松动,且在坡面防护措施(挂网喷浆或喷播植草)施工之前必须人工拆除,产生大量建筑垃圾,完全无法“永临结合”;
[0041](1)极速施工:本发明的卷材在干燥状态下呈柔性卷状,可机械化或人工快速铺设,无需搅拌、无需支模,施工效率远高于传统喷射混凝土。
Smart Images

Figure CN122976164A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of civil engineering and slope protection technology, specifically relating to a permanent and temporary slope protection membrane that can be used for rapid protection after slope excavation and exposure, and can be directly used as a deep framework for subsequent meshing, shotcreting and ecological protection without dismantling, as well as its preparation method and application. Background Technology
[0002] In the construction of infrastructure such as highways, railways and water conservancy, after slope excavation, there will be a "slope exposure period". During this period, the soil and rock are susceptible to weathering and erosion and rainfall scouring. In addition, the water pressure inside the slope is very easy to accumulate in the initial stage, leading to geological disasters such as collapse and landslide.
[0003] Traditional temporary protection typically involves temporary shotcrete, geomembrane installation, or tarpaulin closure during the exposure period. However, this approach has significant drawbacks:
[0004] 1. Geomembrane and tarpaulin are prone to aging, being blown away by the wind, and have low construction efficiency. Fixed nodes are easy to loosen, and they must be manually removed before slope protection measures (wire mesh spraying or grass spraying) are implemented, generating a large amount of construction waste. They are completely unable to be "permanent and temporary combined".
[0005] 2. Traditional shotcrete has limited impermeability. If a large amount of water seeps into the sprayed surface, the water pressure will accumulate behind the concrete surface layer, causing the shotcrete layer to become hollow, peel off, or even gush out locally.
[0006] 3. Disconnect between temporary and permanent protection (waste of resources): When permanent closure or greening protection (such as topsoil spraying or netting spraying) is carried out after the exposure period, it is often necessary to remove the original temporary spraying layer or directly cover it on the original smooth spraying layer. This results in extremely poor interfacial adhesion between the two protective structures, which makes it very easy for the whole structure to slide or peel off and become unstable, which violates the original intention of slope protection.
[0007] In recent years, cement blankets (flexible concrete blankets) have been used as a new type of slope protection material. In its dry state, it is a flexible roll, and upon contact with water, the cement and other binding materials rapidly hydrate and solidify, forming a protective layer with a certain strength. However, after solidification, cement blankets form an impermeable rigid or semi-rigid structure, which cannot solve the problem of water pressure accumulation on the slope, and they are non-degradable, requiring further treatment.
[0008] Furthermore, while existing biodegradable geotextiles offer environmental advantages, their insufficient strength makes them unsuitable as a scaffold layer for permanent protection. Therefore, developing a combined temporary and permanent protection material that can be immediately molded after slope exposure, is permeable and reduces pressure, and can be directly reused without removal for subsequent permanent protection is a pressing technical challenge for the engineering community. Summary of the Invention
[0009] The purpose of this invention is to overcome the shortcomings of the prior art and provide a permanent and temporary protective roll material for slope surfaces, its preparation method and application. This protective roll material can provide rapid full coverage protection after slope excavation, effectively resist rainwater erosion and weathering, dissipate water pressure inside the slope in a timely manner, avoid surface delamination and peeling caused by water pressure accumulation, and can also achieve seamless connection between temporary and permanent protection.
[0010] To achieve the above objectives, the present invention provides a permanent and temporary combined slope protection membrane, the protective membrane comprising a biodegradable waterproof surface layer and a composite structural layer, wherein the biodegradable waterproof surface layer is bonded to the surface of the composite structural layer by hot pressing.
[0011] The biodegradable waterproof surface layer is formed by casting a blend of PLA and PCL at 180-200°C using a casting film machine.
[0012] The composite structure layer includes a biodegradable fiber layer and a permeable gel filler layer. The biodegradable fiber layer is a three-dimensional mesh structure nonwoven fabric made of biodegradable fibers. The permeable gel filler layer is formed by coating one side of the biodegradable fiber layer with a slurry-like permeable gel filler and then using a roller pressing method to fully fill the fiber pores of the biodegradable fiber layer with the slurry-like permeable gel filler.
[0013] The preferred technical solution of the present invention is as follows: the slurry-like permeable cementitious filler is a gel filler formed by mixing biodegradable cementitious material and porous aggregate in a mass ratio of 5-7:3-5, adding water and stirring evenly; the filling amount of the slurry-like permeable cementitious filler into the biodegradable fiber layer is 1.0-2.0 kg / m²; the biodegradable cementitious material is selected from one or more of modified starch-based adhesives, polylactic acid-based adhesives, polycaprolactone-based adhesives, and bio-based epoxy resins; the porous aggregate is selected from one or more of expanded perlite, ceramsite, pumice, and volcanic slag.
[0014] The preferred technical solution of this invention is as follows: the biodegradable waterproof surface layer is hot-pressed onto the side of the biodegradable fiber layer that is not coated with a slurry-like permeable gel filler; the thickness of the biodegradable waterproof surface layer is 0.5–1.0 mm; the hot-pressing temperature is 120–150℃, and the pressure is 0.5–1.0 MPa; the mass ratio of polylactic acid to polycaprolactone in the biodegradable waterproof surface layer is 60–80:20–40; the biodegradable fiber layer is a nonwoven fabric with a three-dimensional mesh structure made by opening, combing, and laying biodegradable fibers, and then using a needle-punching process, with a surface density of 150–250 g / m²; the biodegradable fibers are selected from one or more combinations of polylactic acid fibers, polycaprolactone fibers, polyhydroxyalkanoate fibers, hemp fibers, coconut fibers, and bamboo fibers.
[0015] A preferred technical solution of the present invention is as follows: the upper and lower surfaces of the biodegradable permeable flexible roll material are provided with anti-slip structures, the anti-slip structures being raised dots, corrugations, or grid-like textures; the height of the raised dots is 0.5~1.5 mm, and the spacing is 5~20 mm; the wave height of the corrugations is 0.3~1.0 mm, and the wave pitch is 5~15 mm; the raised height of the grid-like texture is 0.3~0.8 mm, and the grid side length is 5~20 mm.
[0016] This invention provides a method for preparing a permanent and temporary combined protective membrane for slope surfaces, the specific steps of which are as follows:
[0017] S1: The biodegradable fibers are opened, combed, and laid into a web, and then needle-punched to form a three-dimensional mesh structure of nonwoven fabric, forming a biodegradable fiber layer with an areal density of 150-250 g / m².
[0018] S2: Mix biodegradable cementitious material with porous aggregate at a mass ratio of 5-7:3-5, add water and stir evenly to form a slurry-like permeable cementitious filler.
[0019] S3: The slurry-like permeable cementitious filler from step S2 is uniformly coated on one side of the biodegradable fiber layer from step S1. The slurry is then rolled to fully fill the fiber pores, forming a composite structure of fiber reinforcement layer + permeable cementitious filler layer. The filling amount is 1.0 to 2.0 kg / m².
[0020] S4: The blend of PLA and PCL is cast into a film at 180-200°C using a casting film machine to form a biodegradable waterproof surface layer with a thickness of 0.5-1.0 mm;
[0021] S5: The biodegradable waterproof surface layer in step S4 and the composite structure in step S3 are bonded together by hot pressing to form a three-layer integrated biodegradable permeable flexible roll material. The hot pressing temperature is 120-150℃ and the pressure is 0.5-1.0 MPa.
[0022] S6: The composite biodegradable permeable flexible roll material is dried at 40-60℃ until the moisture content is less than 5%, and then rolled up and packaged to form a permanent and temporary slope protection roll material.
[0023] The preferred technical solution of the present invention is as follows: In step S1, the biodegradable fiber is selected from one or more of polylactic acid fiber, polycaprolactone fiber, polyhydroxyalkanoate fiber, hemp fiber, coconut fiber, and bamboo fiber; in step S2, the biodegradable cementitious material is selected from one or more of modified starch-based adhesive, polylactic acid-based adhesive, polycaprolactone-based adhesive, and bio-based epoxy resin; the porous aggregate is selected from one or more of expanded perlite, ceramsite, pumice, and volcanic slag; the most preferred mass ratio of biodegradable cementitious material to porous aggregate is 6:4; in step S4, the mass ratio of polylactic acid to polycaprolactone is 60-80:20-40; in step S5, after the roll material is laminated but before it has completely cooled, an embossing roller with a preset embossed pattern is used to hot-press the surface of the roll material, causing the surface material of the roll material to undergo plastic flow under pressure and temperature, forming raised dots, ripples, or grid-like textures corresponding to the embossing roller pattern.
[0024] The preferred technical solution of the present invention is that the biodegradable permeable flexible roll material has a permeability coefficient of 1×10⁻. 4 ~1×10⁻² cm / s, tensile strength not less than 5 kN / m, tear strength not less than 200 N.
[0025] This invention also provides an application of a permanent and temporary slope protection membrane, which is laid on the surface of the slope after excavation to form a temporary closed protective layer, and the membrane is fixed to the slope surface using fixing components; the membrane is permeable, and after being exposed to water, the permeable cementitious filler part solidifies, so that the membrane changes from a flexible state to a semi-flexible protective layer with a certain degree of rigidity.
[0026] After the exposure period, the roll material partially degrades, and the degradation residue forms a permeable skeleton layer. This permeable skeleton layer serves as the base layer for subsequent permanent protective structures and does not need to be removed.
[0027] A further technical solution of the present invention includes the following specific steps in its application:
[0028] Step 1: After the slope excavation is completed, remove loose rocks, tree roots and other debris from the slope surface;
[0029] Step 2: Provide permanent and temporary slope protection membrane. The membrane is in a flexible roll shape when dry.
[0030] Step 3: Lay the permanent and temporary slope protection membrane along the slope surface from top to bottom or from bottom to top, with overlaps between adjacent membranes; the overlap width is 10-30 cm, and the overlaps are connected by U-shaped nails or hot pressing.
[0031] Step 4: Fix the permanent and temporary slope protection membrane to the slope surface using fixing components to form a temporary closed protective layer. The temporary closed protective layer allows water pressure in the slope to dissipate through the membrane. The fixing components of adjacent membranes are spaced 50-150 cm apart and arranged in a quincunx or rectangular pattern.
[0032] Step 5: After the exposure period, the permanent and temporary combined protective membrane on the slope surface partially degrades, and the degradation residue forms a permeable skeleton layer;
[0033] Step 6: Directly construct a permanent protective structure on the permeable skeleton layer. The permeable skeleton layer serves as the base layer for the permanent protective structure, and there is no need to remove any residue of the biodegradable permeable flexible roll material. The permanent protective structure can be any one of the following: a wire mesh sprayed grout layer, a topsoil spraying layer, a vegetation concrete layer, or an ecological vegetation layer.
[0034] The preferred technical solution of this invention is as follows: the degradation rate of the permanent and temporary slope protection membrane is configured such that: during the slope exposure period, the degradation amount does not exceed 30% of the total mass of the membrane; and within 6 to 24 months after the end of the exposure period, it gradually degrades to 20% to 60% of the initial mass of the residue, forming a stable permeable skeleton layer; the degradation rate is controlled by adjusting the mass ratio of polylactic acid to polycaprolactone and / or adding a degradation promoter, wherein the degradation promoter is selected from one or more of photosensitizers, heat sensitizers, and hydrolysis catalysts, and the amount added is 0.2% to 0.3% of the total mass of the membrane.
[0035] The fixing component includes one or a combination of two of the following: anchor nails and U-shaped nails. The anchor nails are inserted into the slope soil and rock mass through the biodegradable permeable flexible roll material, and the U-shaped nails are located at the edge and / or overlap of the roll material.
[0036] The slope protection membrane of this invention is permeable, allowing water pressure within the slope to dissipate through the membrane and preventing water pressure from accumulating behind the protective layer. It is also biodegradable, partially degrading after the exposure period, with the degradation residue forming a permeable skeleton layer. This permeable skeleton layer serves as the attachment base for subsequent permanent protective structures and can be reused directly without removal.
[0037] PLA has good mechanical properties but insufficient toughness, while PCL has good toughness but lacks mechanical strength. Melt-blending these two materials ensures both degradability and allows them to complement each other in terms of mechanical properties. The biodegradable waterproof surface layer in this invention is a blend of polylactic acid and polycaprolactone. During exposure, this layer primarily functions as a "water barrier"—preventing rainwater from directly eroding the slope while also preventing excessive surface water infiltration into the membrane. Its permeability ensures that moisture from the slope can dissipate outwards, preventing the formation of a water film between layers.
[0038] The biodegradable fiber layer in this invention is woven from biodegradable fibers, providing the roll material with tensile strength and tear resistance. This layer acts as the "skeleton" of the roll material, bearing the main mechanical tension during the laying and fixing stages. The three-dimensional mesh structure ensures both the intertwining of the fibers and provides sufficient filling and anchoring space for the underlying cementitious material. The degradation rate of the fibers is designed to be slower than that of the cementitious filler, ensuring that the fiber skeleton can maintain its structural integrity for a period of time after the cementitious material has partially degraded.
[0039] In this invention, a permeable cementitious filler is used to fill the pores of the fiber-reinforced layer. This permeable cementitious filler is both permeable and biodegradable. Permeability is achieved through porous aggregate, and permanent bonding is achieved through the biodegradable cementitious material. The cement-aggregate ratio is controlled within a reasonable range—too little cementitious material results in insufficient strength, while too much will clog the pores and affect permeability.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) Rapid construction: The roll material of the present invention is in a flexible roll shape when dry, and can be laid quickly by mechanization or manual means without mixing or formwork. The construction efficiency is much higher than that of traditional shotcrete.
[0042] (2) Water permeability and pressure reduction: The roll material of the present invention has good water permeability, and the water pressure in the slope can be dissipated in time through the roll material, which fundamentally avoids the problems of hollowing and peeling caused by water pressure accumulation in traditional sprayed concrete.
[0043] (3) Permanent and temporary combination: After the exposure period, the roll material of the present invention partially degrades to form a permeable skeleton layer, which can be used as the attachment base layer of the permanent protective structure without removal, thus avoiding the construction waste and poor interface bonding problems caused by the removal of traditional temporary protection.
[0044] (4) Ecological and environmental protection: The roll material of the present invention can be naturally degraded and no construction waste is generated, which is in line with the concept of green construction and sustainable development.
[0045] (5) Wide applicability: This invention is applicable to various slope engineering projects such as highways, railways, and water conservancy, especially to high excavation slopes and water-rich strata slopes. Attached Figure Description
[0046] Figure 1 This is a schematic diagram of the layered structure of the roll material in this invention;
[0047] Figure 2 This is a schematic diagram illustrating the morphological changes of the roll material before and after degradation in this invention;
[0048] Figure 3 This is a flowchart of the construction method for applying the roll material in this invention;
[0049] Figure 4This is a schematic diagram of the permanent and temporary combined protection system for the excavation exposure period of the present invention.
[0050] In the diagram: 1. Biodegradable waterproof surface layer; 2. Biodegradable fiber layer; 3. Permeable cementitious filling layer; 4. Partially degraded fiber residual skeleton; 5. Permeable gravel skeleton layer formed after the cementitious material degrades; 6. Permanent protective surface layer; 7. Permanent and temporary combined permeable rough interface layer; 8. U-shaped nail; 9. Slope excavation surface; 10. Anchor nail. Detailed Implementation
[0051] The present invention will be further described below with reference to specific embodiments.
[0052] An example of a slope surface permanent and temporary combined protection membrane is provided in the embodiment, such as Figure 1 As shown, it includes a biodegradable waterproof surface layer 1 and a composite structural layer. The biodegradable waterproof surface layer 1 is bonded to the surface of the composite structural layer by hot pressing. The biodegradable waterproof surface layer 1 is formed by casting a blend of PLA and PCL at 180-200°C using a casting film machine; the film thickness is 0.5-1.0 mm; the hot pressing temperature is 120-150°C, and the pressure is 0.5-1.0 MPa; the mass ratio of polylactic acid to polycaprolactone in the biodegradable waterproof surface layer 1 is 60-80:20-40.
[0053] The composite structure layer includes a biodegradable fiber layer 2 and a permeable gel filler layer 3. The biodegradable fiber layer 2 is a nonwoven fabric with a three-dimensional mesh structure, made by opening, carding, and laying biodegradable fibers into a web using a needle punching process, with a surface density of 150-250 g / m². The biodegradable fibers are selected from one or more combinations of polylactic acid fiber, polycaprolactone fiber, polyhydroxyalkanoate fiber, hemp fiber, coconut fiber, and bamboo fiber. The permeable gel filler layer 3 is formed by coating one side of the biodegradable fiber layer 2 with a slurry-like permeable gel filler and using a roller pressing method to fully fill the fiber pores of the biodegradable fiber layer 2 with the slurry-like permeable gel filler. The biodegradable waterproof surface layer 1 is hot-pressed onto the side of the biodegradable fiber layer 2 that is not coated with the slurry-like permeable gel filler.
[0054] The slurry-like permeable cementitious filler is a gel filler formed by mixing biodegradable cementitious material and porous aggregate in a mass ratio of 5-7:3-5, then adding water and stirring evenly. The filling amount of the slurry-like permeable cementitious filler into the biodegradable fiber layer 2 is 1.0-2.0 kg / m². The biodegradable cementitious material is selected from one or more of modified starch-based adhesives, polylactic acid-based adhesives, polycaprolactone-based adhesives, and bio-based epoxy resins. The porous aggregate is selected from one or more of expanded perlite, ceramsite, pumice, and volcanic slag.
[0055] The biodegradable, permeable, flexible roll material has anti-slip structures on both its upper and lower surfaces. These structures are formed by hot-pressing the roll material surface with an embossing roller bearing a pre-set raised or recessed pattern after lamination but before it has fully cooled. This causes the surface material to plastically flow under pressure and temperature, creating raised dots, ripples, or a grid-like texture corresponding to the embossing roller pattern. After cooling and setting, the anti-slip structure is integrally formed with the roll material. The anti-slip structure consists of raised dots, ripples, or a grid-like texture; the height of the raised dots is 0.5–1.5 mm, and the spacing is 5–20 mm; the wave height of the ripples is 0.3–1.0 mm, and the wave pitch is 5–15 mm; the raised height of the grid-like texture is 0.3–0.8 mm, and the grid side length is 5–20 mm.
[0056] The biodegradable, permeable, flexible roll material has a permeability coefficient of 1×10⁻ 4 ~1×10⁻² cm / s, tensile strength not less than 5 kN / m, tear strength not less than 200 N.
[0057] The degradation rate of the permanent and temporary slope protection membrane is configured such that: during the slope exposure period, the degradation amount does not exceed 30% of the total mass of the membrane; and within 6 to 24 months after the end of the exposure period, it gradually degrades to 20% to 60% of the initial mass of the residue, forming a stable permeable skeleton layer; the degradation rate is controlled by adjusting the mass ratio of polylactic acid to polycaprolactone and / or adding a degradation promoter, wherein the degradation promoter is selected from one or more of photosensitizers, heat sensitizers, and hydrolysis catalysts, and the amount added is 0.2% to 0.3% of the total mass of the membrane.
[0058] The fixing component includes one or a combination of two of the following: anchor nails and U-shaped nails. The anchor nails are inserted into the slope soil and rock mass through the biodegradable permeable flexible roll material, and the U-shaped nails are located at the edge and / or overlap of the roll material.
[0059] A temporary and permanent slope protection membrane is laid on the exposed surface of the slope after excavation to form a temporary closed protective layer. The membrane is then fixed to the slope surface using fixing components. The membrane is permeable; upon contact with water, the permeable gel filler partially solidifies, transforming the membrane from a flexible state into a semi-flexible protective layer with a certain degree of rigidity. After the exposure period, the membrane partially degrades, such as… Figure 2 As shown, the degradation residue forms a permeable skeleton layer, which serves as the substrate for subsequent permanent protective structures and does not need to be removed.
[0060] Example 1 provides a permanent and temporary slope protection membrane for use in the protection of a high slope in a highway cutting.
[0061] The slope protection membrane in Example 1 consists of the following components: the fiber reinforcement layer is a three-dimensional mesh fabric woven from polylactic acid fibers with a surface density of 200 g / m². The permeable cementitious filler is a mixture of modified starch-based adhesive (60% by mass) and expanded perlite (40% by mass), which is filled into the pores of the fiber reinforcement layer at a filling amount of 1.5 kg / m².
[0062] The performance indicators of the roll material are as follows: thickness of 8 mm in dry state, water permeability coefficient of 5×10⁻³ cm / s, tensile strength of 8kN / m, and tear strength of 350 N.
[0063] The specific application steps for the protection of high slopes in a highway cutting are as follows:
[0064] (1) After the slope excavation is completed, the slope surface is cleaned to the designed slope, with a slope ratio of 1:1.25.
[0065] (2) Lay the roll material from top to bottom on the slope. The overlap width of adjacent roll materials is 20 cm. Use biodegradable overlap buckles to fix the overlap.
[0066] (3) Use biodegradable anchors to fix the roll material. The anchor spacing is 100 cm × 100 cm, arranged in a quincunx pattern.
[0067] (4) After the roll material is laid, a temporary closed protective layer is formed on the slope. After a 3-month exposure period, during which multiple rainfalls occurred, no obvious erosion marks were seen on the surface of the roll material, and the water pressure monitoring data inside the slope showed that the water pressure could dissipate in time.
[0068] (5) After the exposure period, the amount of the roll material degraded by about 15% of the initial mass, and the residue formed a stable permeable skeleton layer.
[0069] (6) A shotcrete layer with mesh was directly applied on the permeable skeleton layer, with a shotcrete thickness of 10 cm. The test results showed that the interfacial bonding strength between the shotcrete layer and the permeable skeleton layer reached 0.8 MPa, which is much higher than the bonding strength of secondary shotcrete on a traditional smooth shotcrete surface (usually 0.2 to 0.4 MPa).
[0070] Example 2 provides a combined permanent and temporary slope protection membrane for use in the protection of channel slopes in a water conservancy project.
[0071] Unlike Example 1, the fiber reinforcement layer is made of a blend of hemp fiber and polycaprolactone fiber; the permeable cementitious filler is a mixture of polylactic acid-based adhesive (50% by mass) and ceramsite (50% by mass); and 2% by mass of photosensitizer is added to the roll material as a degradation promoter.
[0072] The construction steps are basically the same as in Example 1, except that the permanent protective structure is a topsoil spraying layer with a spraying thickness of 8 cm, and the grass species is a mixture of Bermuda grass and Magnolia multiflora.
[0073] After 6 months of observation, the degradation rate of the roll material during the exposure period was about 20%, the residual skeleton effectively supported the stability of the topsoil spraying layer, the vegetation grew well, and the green coverage rate of the slope reached more than 85%.
[0074] Example 3 provides a method for preparing a combined permanent and temporary slope protection membrane, as detailed below:
[0075] (a) Biodegradable waterproof surface layer
[0076] It is prepared by melt blending and modification of polylactic acid (PLA) and polycaprolactone (PCL). PLA has high strength and a fast degradation rate, but insufficient toughness; PCL has good toughness and a slower degradation rate. The properties of the two are complementary, and the formulation is as follows:
[0077] Polylactic acid (PLA) 60-80 servings Matrix resin provides strength and biodegradability Polycaprolactone (PCL) 20-40 servings Toughening components regulate degradation rate Chain extender (hexamethylene diisocyanate) 0.5~1.0 parts Improve blend compatibility Antioxidant (hindered phenols 1010) 0.3~0.5 parts Preventing thermal degradation during processing
[0078] The optimal ratio is PLA:PCL = 70:30 (mass ratio). At this ratio, the blended film exhibits both good mechanical properties and a controllable degradation rate. Research data shows that pure PLA experiences a 7.3% mass loss within 45 days, while the 70:30 PLA / PCL blend experiences a 21.7% mass loss under the same conditions, indicating that the addition of PCL significantly accelerates the degradation process.
[0079] (ii) Biodegradable three-dimensional fiber reinforcement layer (intermediate skeleton layer)
[0080] A three-dimensional mesh structure nonwoven fabric made from biodegradable fibers through needle punching or thermal bonding processes. The fiber raw materials are selected from one or more combinations of the following:
[0081] Polylactic acid (PLA) fiber High strength and fast degradation rate Polycaprolactone fiber (PCL) Good toughness and slow degradation rate Polyhydroxyalkanoate (PHA) fiber Excellent biodegradability hemp fiber Natural fibers, low cost, moderate strength Coconut fiber Natural fiber, good water resistance bamboo fiber Natural fibers, renewable
[0082] Areal density: 150–250 g / m². PLA fibers can be processed into fibers with good mechanical properties and are completely biodegradable after use.
[0083] (iii) Biodegradable permeable cementitious filler layer (lower functional layer)
[0084] It is made by mixing biodegradable cementitious materials with porous aggregates.
[0085] Biodegradable gelling material formulation: Modified starch-based adhesive (preferred)
[0086] Modified corn starch 40-60 servings Base material, biodegradable Polyvinyl alcohol 10-20 servings Enhance bond strength water Appropriate amount (adjust to a solid content of 30-40%) Dispersion medium Sodium hypochlorite 2-4 servings Oxidative modification Potassium persulfate 0.1~0.3 parts Initiator Borax 1-3 servings Crosslinking agent
[0087] Starch-based adhesives use natural starch as the main raw material and are characterized by being biodegradable and pollution-free.
[0088] Porous aggregate: selected from one or more of expanded perlite, ceramsite, pumice, and volcanic slag, with a particle size of 0.5 to 5 mm.
[0089] Glue-to-aggregate ratio (mass ratio): biodegradable cementitious material: porous aggregate = 5:5 to 7:3.
[0090] The three-layer structure is combined into one unit through the following steps:
[0091] S1: The biodegradable fibers are opened, combed, and laid into a web, and then needle-punched to form a three-dimensional mesh structure of nonwoven fabric, forming a biodegradable fiber layer with an areal density of 150-250 g / m².
[0092] S2: Mix biodegradable cementitious material with porous aggregate at a mass ratio of 5-7:3-5, add water and stir evenly to form a slurry-like permeable cementitious filler.
[0093] S3: The slurry-like permeable cementitious filler from step S2 is uniformly coated on one side of the biodegradable fiber layer from step S1. The slurry is then rolled to fully fill the fiber pores, forming a composite structure of fiber reinforcement layer + permeable cementitious filler layer. The filling amount is 1.0 to 2.0 kg / m².
[0094] S4: The blend of PLA and PCL is cast into a film at 180-200°C using a casting film machine to form a biodegradable waterproof surface layer with a thickness of 0.5-1.0 mm;
[0095] S5: The biodegradable waterproof surface layer from step S4 is bonded to the composite structure from step S3 via hot-pressing to form a three-layer integrated biodegradable permeable flexible roll material. The hot-pressing temperature is 120–150°C, and the pressure is 0.5–1.0 MPa. If an anti-slip structure is required, after the roll material is laminated but before it has fully cooled, an embossing roller with a preset raised and recessed pattern is used to hot-press the surface of the roll material. This causes the surface material of the roll material to undergo plastic flow under pressure and temperature, forming raised dots, ripples, or grid-like textures corresponding to the embossing roller pattern. After cooling and setting, the anti-slip structure is integrally formed with the roll material.
[0096] S6: The composite biodegradable permeable flexible roll material is dried at 40-60℃ until the moisture content is less than 5%, and then rolled up and packaged to form a permanent and temporary slope protection roll material.
[0097] The inventors of this application conducted comparative experiments on the formulation of the roll material. Specifically, they prepared five groups of roll material samples with different formulations using the method described in Example 3, and tested their water permeability coefficient, tensile strength, and 45-day degradation rate. The material ratios and performance requirements of the five samples are as follows:
[0098] Sample 1 8:2 100:0 <![CDATA[0.8×10⁻ 4 ]]> 6.2 7.3 Sample 2 4:6 100:0 8.5×10⁻³ 3.1 8.1 Sample 3 6:4 70:30 5.0×10⁻³ 8.0 21.7 Sample 4 7:3 60:40 3.2×10⁻³ 8.8 25.3 Sample 5 5:5 80:20 7.8×10⁻³ 6.5 16.8
[0099] The comparison of the test results of the above five samples shows that:
[0100] Effect of binder-to-aggregate ratio: In sample 1 (binder-to-aggregate ratio 8:2), there was too much cementitious material, which blocked the pores, resulting in a permeability coefficient of only 0.8 × 10⁻ 4 cm / s; Sample 2 (4:6) had too much aggregate, and its tensile strength was only 3.1 kN / m. Sample 3 (6:4 glue-aggregate ratio) achieved the optimal balance between permeability (5.0×10⁻³ cm / s) and tensile strength (8.0 kN / m).
[0101] Effect of PLA / PCL ratio: Pure PLA (control samples 1 and 2) had a degradation rate of only 7-8% after 45 days; sample 3 (70:30) had a degradation rate of 21.7%, an increase of about 3 times. This indicates that the addition of PCL significantly accelerated the degradation process.
[0102] Overall optimal: Sample 3 (glue-to-grain ratio 6:4, PLA:PCL=70:30) is the best ratio, combining good permeability, mechanical strength and controllable degradation rate.
[0103] The above description is merely one embodiment of the present invention, and while it is detailed and specific, it should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.
Claims
1. A permanent and temporary slope protection membrane, characterized in that: The protective roll material includes a biodegradable waterproof surface layer (1) and a composite structure layer. The biodegradable waterproof surface layer (1) is bonded to the surface of the composite structure layer by hot pressing. The biodegradable waterproof surface layer (1) is formed by casting a blend of PLA and PCL at 180-200°C using a casting film machine. The composite structure layer includes a biodegradable fiber layer (2) and a permeable gel filler layer (3). The biodegradable fiber layer (2) is a three-dimensional mesh structure nonwoven fabric made of biodegradable fibers. The permeable gel filler layer (3) is formed by coating a slurry-like permeable gel filler on one side of the biodegradable fiber layer (2) and using a roller pressing method to fully fill the fiber pores of the biodegradable fiber layer (2).
2. The slope protection membrane with permanent and temporary features according to claim 1, characterized in that: The slurry-like permeable cementitious filler is a gel filler formed by mixing biodegradable cementitious material and porous aggregate in a mass ratio of 5-7:3-5, adding water and stirring evenly; the filling amount of the slurry-like permeable cementitious filler into the biodegradable fiber layer (2) is 1.0-2.0 kg / m²; the biodegradable cementitious material is selected from one or more of modified starch-based adhesives, polylactic acid-based adhesives, polycaprolactone-based adhesives, and bio-based epoxy resins; the porous aggregate is selected from one or more of expanded perlite, ceramsite, pumice, and volcanic slag.
3. A combined permanent and temporary slope protection membrane according to claim 1 or 2, characterized in that: The biodegradable waterproof surface layer (1) is hot-pressed onto the side of the biodegradable fiber layer (2) that is not coated with a slurry-like permeable gel filler. The thickness of the biodegradable waterproof surface layer (1) is 0.5-1.0 mm. The hot-pressing temperature is 120-150℃ and the pressure is 0.5-1.0 MPa. The mass ratio of polylactic acid to polycaprolactone in the biodegradable waterproof surface layer (1) is 60-80:20-40. The biodegradable fiber layer (2) is a nonwoven fabric with a three-dimensional mesh structure made by opening, combing, and laying biodegradable fibers, and using a needle punching process. The surface density is 150-250 g / m². The biodegradable fibers are selected from one or more combinations of polylactic acid fiber, polycaprolactone fiber, polyhydroxyalkanoate fiber, hemp fiber, coconut fiber, and bamboo fiber.
4. A combined permanent and temporary slope protection membrane according to claim 1 or 2, characterized in that: The biodegradable permeable flexible roll material has anti-slip structures on its upper and lower surfaces. The anti-slip structures are raised dots, corrugations, or grid-like textures. The height of the raised dots is 0.5~1.5 mm and the spacing is 5~20 mm. The wave height of the corrugations is 0.3~1.0 mm and the wave pitch is 5~15 mm. The raised height of the grid-like texture is 0.3~0.8 mm and the grid side length is 5~20 mm.
5. A method for preparing a combined permanent and temporary slope protection membrane according to any one of claims 1 to 4, characterized in that, The specific steps are as follows: S1: The biodegradable fibers are opened, combed, and laid into a web, and then needle-punched to form a three-dimensional mesh structure of nonwoven fabric, forming a biodegradable fiber layer with an areal density of 150-250 g / m². S2: Mix biodegradable cementitious material with porous aggregate at a mass ratio of 5-7:3-5, add water and stir evenly to form a slurry-like permeable cementitious filler. S3: The slurry-like permeable cementitious filler from step S2 is uniformly coated on one side of the biodegradable fiber layer from step S1. The slurry is then rolled to fully fill the fiber pores, forming a composite structure of fiber reinforcement layer + permeable cementitious filler layer. The filling amount is 1.0 to 2.0 kg / m². S4: The blend of PLA and PCL is cast into a film at 180-200℃ using a casting film machine to form a biodegradable waterproof surface layer with a thickness of 0.5-1.0mm; S5: The biodegradable waterproof surface layer in step S4 is bonded to the composite structure in step S3 by hot pressing to form a three-layer integrated biodegradable permeable flexible roll material. The hot pressing temperature is 120-150℃ and the pressure is 0.5-1.0 MPa. S6: The composite biodegradable permeable flexible roll material is dried at 40-60℃ until the moisture content is less than 5%, and then rolled up and packaged to form a permanent and temporary slope protection roll material.
6. The method for preparing a combined permanent and temporary slope protection membrane according to claim 5, characterized in that: In step S1, the biodegradable fiber is selected from one or more combinations of polylactic acid fiber, polycaprolactone fiber, polyhydroxyalkanoate fiber, hemp fiber, coconut fiber, and bamboo fiber; in step S2, the biodegradable cementitious material is selected from one or more of modified starch-based adhesive, polylactic acid-based adhesive, polycaprolactone-based adhesive, and bio-based epoxy resin; the porous aggregate is selected from one or more of expanded perlite, ceramsite, pumice, and volcanic slag; the optimal mass ratio of biodegradable cementitious material to porous aggregate is 6:4; in step S4, the mass ratio of polylactic acid to polycaprolactone is 60-80:20-40; in step S5, after the roll material is laminated but before it has completely cooled, an embossing roller with a preset embossed pattern is used to hot-press the surface of the roll material, causing the surface material of the roll material to undergo plastic flow under pressure and temperature, forming raised dots, ripples, or grid-like textures corresponding to the embossing roller pattern.
7. The method for preparing a combined permanent and temporary slope protection membrane according to claim 5, characterized in that: The biodegradable, permeable, flexible roll material has a permeability coefficient of 1×10⁻ 4 ~1×10⁻² cm / s, tensile strength not less than 5 kN / m, tear strength not less than 200 N.
8. The application of a permanent and temporary slope protection membrane as described in any one of claims 1 to 4, characterized in that: The permanent and temporary slope protection membrane is laid on the surface of the slope after excavation to form a temporary closed protective layer, and the membrane is fixed to the slope surface using fixing components. The membrane is permeable, and after being exposed to water, the permeable cementitious filler part solidifies, so that the membrane changes from a flexible state to a semi-flexible protective layer with a certain degree of rigidity. After the exposure period, the roll material partially degrades, and the degradation residue forms a permeable skeleton layer. This permeable skeleton layer serves as the base layer for subsequent permanent protective structures and does not need to be removed.
9. The application of a permanent and temporary slope protection membrane according to claim 8, characterized in that, Specifically, the following steps are included: Step 1: After the slope excavation is completed, remove loose rocks, tree roots and other debris from the slope surface; Step 2: Provide permanent and temporary slope protection membrane. The membrane is in a flexible roll shape when dry. Step 3: Lay the permanent and temporary slope protection membrane along the slope surface from top to bottom or from bottom to top, with overlaps between adjacent membranes; the overlap width is 10-30 cm, and the overlaps are connected by U-shaped nails or hot pressing. Step 4: Fix the permanent and temporary slope protection membrane to the slope surface using fixing components to form a temporary closed protection layer. The temporary closed protection layer allows water pressure in the slope to dissipate through the membrane. The fixing components of adjacent membranes are spaced 50-150 cm apart and arranged in a quincunx or rectangular pattern. Step 5: After the exposure period, the permanent and temporary combined protective membrane on the slope surface partially degrades, and the degradation residue forms a permeable skeleton layer; Step 6: Directly construct a permanent protective structure on the permeable skeleton layer. The permeable skeleton layer serves as the base layer for the permanent protective structure, and there is no need to remove any residue of the biodegradable permeable flexible roll material. The permanent protective structure can be any one of the following: a wire mesh sprayed grout layer, a topsoil spraying layer, a vegetation concrete layer, or an ecological vegetation layer.
10. The application of a combined permanent and temporary slope protection membrane according to claim 8 or 9, characterized in that, The degradation rate of the permanent and temporary slope protection membrane is configured such that: during the slope exposure period, the degradation amount does not exceed 30% of the total mass of the membrane; and within 6 to 24 months after the exposure period, it gradually degrades to 20% to 60% of the initial mass of the residue, forming a stable permeable skeleton layer. The degradation rate is controlled by adjusting the mass ratio of polylactic acid to polycaprolactone and / or adding a degradation promoter, wherein the degradation promoter is selected from one or more of photosensitizers, heat sensitizers, and hydrolysis catalysts, and the amount added is 0.2% to 0.3% of the total mass of the membrane. The fixing component includes one or a combination of two of the following: anchor nails and U-shaped nails. The anchor nails are inserted into the slope soil and rock mass through the biodegradable permeable flexible roll material, and the U-shaped nails are located at the edge and / or overlap of the roll material.